Emotiveness of Pozdnyshev’s Monologue in L.N. Tolstoy’s “Kreutzer Sonata” Novel - Hovhannesyan, Gayane (Bulletin of Yerevan University H: Russian Philology, 2024)
The work examines the text of the story “Kreutzer sonata” by L.N. Tolstoy. In this work the speech of the main character are conveyed through the form of monologue. This creates the appropriate structure of expression, grammatical structure of statements, and style. The hero’s inner experiences are reflected in language: the psychology of the speaker shapes the characteristics of his speech. We consider the main psychological characteristic of Pozdnyshev’s monologue to be its emotionality and expressiveness, which is described through emotive means. The work notes the difference in the understanding of the terms «emotionality» and «emotivity». We touch upon the artistic means of poetic speech – emotive means – which helps to build high expression of speech. This figures can externally, explicitly, carry a pronounced emotional coloring, but they can also express emotion by entering into contextual connections, various configurations and combinations. The emotiveness of speech can be built at the word-formative, lexical, and syntactic – concordance, contrasting, combinability – levels. In the work there is a changing of the character’s psychological states, which is noticeable both in the plot and in the speech: this is a combination of words, the lexical content of a phrase, its technical characteristics – length, tempo, volume. The conjugation of these elements certain the systemic characteristics of this text.